Knowledge and skill requirements for marketing positions: the gap between employers' and undergraduate marketing students' expectations in Kuching, Sarawak - Gregory, Margaret Lucy (Research Management Institute (RMI), 2013)
Marketing education has seen a tremendous growth over the years. Thus, marketing education has a responsibility of preparing marketers of the future with the relevant knowledge and skills essential for subsequent organizational and career success. However, there is little research done on the effectiveness of marketing education in Malaysia focusing on purely marketing elements. Our research attempts to identify what undergraduate marketing students in Sarawak expect of their jobs and how these expectations can be compared to the needs of the job markets and identifying areas of commonality and difference. This study will use qualitative and the quantitative method. Data will be analysed using the SPSS 17.0 software and descriptive analysis will be used extensively in this study. With a greater insight into the expectations of employers and students alike, we hope to draw some conclusion about the effectiveness of the current degree program in encouraging students to develop the capability required if they are to be employed as fresh graduates. Furthermore, the findings would provide suggestions for how courses offered by the universities and institutions of higher learning could be adapted to reflect employers' needs.